Analysis of risk factors for stunting among under-five children: A case-control study in Baiturrahman Primary Health Center, Banda Aceh City - Neni Ekowati Januariana; Dian Maya Sari Siregar; Winda Agustina; Endang Maryanti; Ecia Meilonna Koka; Rosdiana Rosdiana; Marlina Marlina; Asriwati Asriwati; Suzan Fitriana Pakpahan; Siti Aisyah; Jalilah Jalilah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting is a form of chronic malnutrition that adversely affects the growth and development of children under five years of age. This study aimed to analyze the factors associated with stunting among children in Banda Aceh, Indonesia. A cross-sectional study was conducted in Banda Aceh in 2023 involving 128 respondents, comprising 64 stunted children (cases) and 64 non-stunted children (controls). Data were analyzed using chi-square tests and logistic regression at the 95% confidence level. Results: Maternal knowledge (p=0,002), socioeconomic status (p=0,005), breastfeeding practices (p=0,012), birth weight (p=0,009), and maternal educational level (p=0,014) were significantly associated with stunting. The dominant factor influencing stunting was low birth weight (odds ratio [OR] =2,4; p=0,012). In conclusion, low birth weight was identified as the primary determinant of stunting. Other factors, such as maternal knowledge, education, socioeconomic status, and breastfeeding also played a role, although they were not significant in the multivariate analysis. Stunting prevention should begin during pregnancy through multi-sectoral interventions, nutrition education, strengthened antenatal care services, and family economic empowerment.